Legal Protection of Copyrighted Dance Works as an Effort to Preserve Culture in Karawang District - Pratiwi, Dwi Nuraeni; Rahmatiar, Yuniar; Abas, Muhamad (Journal of Law, Politic and Humanities, 2025)
An exclusive right that is born automatically inherent in a creator of a copyrighted work that has a real form by way of declaration is called copyright.  Regarding the art of dance is a creative work of gesture derived from the process of thinking and imagination gained from experience processed based on the ability and skill which is then realized into a real form. The legal basis for the protection of dance artworks is Law Number 28 of 2014 concerning Copyright. The identification of the problems of the research that the authors have carried out, namely about how the form of legal protection of copyrighted works of dance art in law - law number 28 of 2014 on copyright and how efforts made by dance artists in Karawang Regency to protect copyrighted works of dance art. In conclusion, among dance artists in Karawang Regency, Law Number 28 of 2014 concerning Copyright has not been implemented so that dance artworks in Karawang Regency have not been maximally protected, this is due to the lack of awareness of Karawang Regency dance artists to protect their work. So, further socialization is needed regarding the form of legal protection of copyrighted dance works regulated in Law Number 28 of 2014 concerning Copyright